Limitations of PET/CT in the Detection of Occult N1 Metastasis in Clinical Stage I(T1-2aN0) Non-Small Cell Lung Cancer for Staging Prior to Stereotactic Body Radiotherapy. (February 2017) - Akthar, Adil S.; Ferguson, Mark K.; Koshy, Matthew; Vigneswaran, Wickii T.; Malik, Renuka
Purpose/Objectives: Patients receiving stereotactic body radiotherapy for stage I non-small cell lung cancer are typically staged clinically with positron emission tomography–computed tomography. Currently, limited data exist for the detection of occult hilar/peribronchial (N1) disease. We hypothesize that positron emission tomography–computed tomography underestimates spread of cancer to N1 lymph nodes and that future stereotactic body radiotherapy patients may benefit from increased pathologic evaluation of N1 nodal stations in addition to N2 nodes. Materials/Methods: A retrospective study was performed of all patients with clinical stage I (T1-2aN0) non-small cell lung cancer (American Joint Committee on Cancer, 7th edition) by positron emission tomography–computed tomography at our institution from 2003 to 2011, with subsequent surgical resection and lymph node staging. Findings on positron emission tomography–computed tomography were compared to pathologic nodal involvement to determine the negative predictive value of positron emission tomography–computed tomography for the detection of N1 nodal disease. An analysis was conducted to identify predictors of occult spread. Results: A total of 105 patients with clinical stage I non-small cell lung cancer were included in this study, of which 8 (7.6%) patients were found to have occult N1 metastasis on pathologic review yielding a negative predictive value for N1 disease of 92.4%. No patients had occult mediastinal nodes. The negative predictive value for positron emission tomography–computed tomography in patients with clinical stage T1 versus T2 tumors was 72 (96%) of 75 versus 25 (83%) of 30, respectively ( P = .03), and for peripheral versus central tumor location was 77 (98%) of 78 versus 20 (74%) of 27, respectively ( P = .0001). The negative predictive values for peripheral T1 and T2 tumors were 98% and 100%, respectively; while for central T1 and T2 tumors, the rates were 85% and 64%, respectively. Occult lymph node involvement was not associated with primary tumor maximum standard uptake value, histology, grade, or interval between positron emission tomography–computed tomography and surgery. Conclusion: Our results support pathologic assessment of N1 lymph nodes in patients with stage Inon-small cell lung cancer considered for stereotactic body radiotherapy, with the greatest benefit in patients with central and T2 tumors. Diagnostic evaluation with endoscopic bronchial ultrasound should be considered in the evaluation of stereotactic body radiotherapy candidates.